Pengaruh Waktu dan Temperatur Pemanasan Pada Pengujian Alat Pengolahan Sampah Plastik Menjadi Bahan Bakar Minyak - Pribadyo Pribadyo; Teguh Firmanto; Desy Saputra; Mardianto Mardianto (Jurnal Mekanova: Mekanikal, Inovasi dan Teknologi, 2015)
Plastics are polymers long chains of atoms that bind to each other. This chain form many repetitive molecular units, or "monomers". Plastics are formed from organic condensation or addition polymers and may also comprise other substances to improve performance or economics. Judging from the nature of the plastic that is composed of constituent components of petroleum hydrocarbons, the plastic waste has the potential to be converted into fuel. The aim of this study was to determine the influence of time and temperature on the quality of oil products from the pyrolysis process PP and LDPE plastic waste. The technique used to restore the plastic material is by breaking the carbon chains or polymers that become hydrocarbons. And for the decomposition technique to be used is the method of pyrolysis. Pyrolysis is a process of decomposition of the material at high temperatures in the absence of air or with air is limited. Decomposition of the pyrolysis process is also often referred to devolatilization. The main products of pyrolysis can be produced are charcoal (char), oil, and gas. On pyrolysis occurs tool decomposition process of organic compounds on the materials. This decomposition caused by the heating process without directly related to the air with little oxygen. Results of testing tools to test materials for a type of plastic LDPE (low-density polyethylen) at temperatures of 246 0C combustion chamber, reactor temperature 114 0C, 94 0C temperature of the first condenser and the second condenser temperature 61 0C with a duration of 57 minutes burning oil expenditures occur. At 345 0C temperature in the combustion chamber, the reactor temperature 113 0C, 99 0C temperature in condenser I, temperature 63 0C in condenser II with the duration of 93 minutes burning of oil does not produce. With the test material for plastic types PP (Polypropylene) at temperatures of 239 0C combustion chamber, reactor temperature 114 0C, 94 0C temperature of the first condenser and the second condenser temperature 57 0C with a duration of 42 minutes burning oil expenditures occur. At 330 0C temperature in the combustion chamber, the reactor temperature 121 0C, 105 0C temperature in condenser I, 59 0C temperature in condenser II with the duration of 99 minutes burning of oil does not produce.   Keywords: Waste plastic, temperature, pyrolysis oil, Testing